which property justifies the statement below x(y-3)=xy-3x

Question

which property justifies the statement below x(y-3)=xy-3x

0

Answers ( No )

  1. Emma
    0
    2021-10-11T02:03:51+00:00

    the distributive property

    a(b + c ) = ab + ac

    Apply this property to the given expression

    x(y – 3 ) = xy – 3x

  2. Emma
    0
    2021-10-11T02:04:08+00:00

    For this case we have that, by definition, the distributive property states that the multiplication of a number by a sum is equal to the sum of the multiplications of that number by each of the addends, that is:

    a (b + c) = ab + ac

    Thus, it is observed that the property applied was the distributive property
    ,

    x(y-3)=xy-3x

    Answer:

    Distributive property

Leave an answer

Browse
Browse